PERLINDUNGAN HUKUM TERHADAP KORBAN PENYALAHGUNA NARKOTIKA DENGAN BERLAKUNYA UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Candra Dewi, A.A. Istri Mas (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 1 No 1 (2012), 2012)
This Study in the legal protection of the victims of narcotics abusers aims to decrypt and analyze aspects of issues related to the concepts that underlie the need for justification of legal protection of the victims and supervision of the implementation of the decisions of rehabilitation, as well as decrypt and analyze the legal form of protection. This study is a normative one using law approach and legal concept analysis. The results of the study indicate the legal protection of victims of drug abusers can not be detached from the underlying idea of legal protection of the victims of narcotics abusers in the form rehabilitasi. Legal provisions governing the rehabilitation of drug addicts measures stipulated in Article 54, 56.103, and was associated with article 127 of Law No. 35 of 2009, SEMA No. 4 of 2010 as The Guideline on the implementation of the rehabilitation of narcotics abusers, but monitoring of the rehabilitation measures not accommodated in such provisions so that there are gaps in the law enforcement mechanism of action monitoring narotics rehabilitation.
Keywords: Legal Protection; Narcotics Abusers; Victims